Microstructure of kajmak skin layer made during kajmak production - Radovanović, Mira (Array, 2020)
Kajmak is a unique dairy product with a long tradition in Balkan countries and the Middle East. Kajmak skin layers are formed during 60 minutes of kajmak production, influencing the quality and determining the structure of the final product. The influence of milk composition and heat treatments (75-95 °C/5min) on the composition, microstructure and protein distribution of kajmak skin layers was investigated in this study. Microstructure was determined using scanning electron microscopy (SEM), while the distribution of protein fractions was studied by SDS PAGE in reducing and non-reducing conditions. Kajmak skin layers obtained from milk treated at common intense heat regime were characterized with β-LG and α-LA mainly as disulfide-linked complexes, while lower temperature (75 °C) caused the presence of whey proteins in dominantly individual form. More severe treatments (85 °C, 90 °C and 95 °C) caused the full involvement of β-LG in the complexes, since a certain amount of α-LA was found as a monomer. The kajmak skin layer composition, severity of the applied milk heat treatment and the linked whey proteins exhibited a very strong influence on kajmak skin layer microstructure. The microstructure of kajmak skin layer with a low fat content and fat/protein (F/P) ratio was characterized by a compact structure with a dense protein matrix. High fat content and F/P ratio resulted in a dispersive form of the stretched protein network. Kajmak skin layers produced from milk with added whey proteins were characterized by fibrous, thread-like segments, due to the incorporated denatured whey proteins, especially linked β-LG.